2020
DOI: 10.1186/s42269-020-00378-w
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of laying snails (Archachatina marginata) fed on roughages and different concentrate mixes

Abstract: Background This study aims to investigate the reproduction output of Archachatina marginata fed on roughage and concentrate feed with leaf meal-inclusive diets. One hundred fifty points of lay snails weighing between 150 and 170 g were randomly allotted to 5 treatment diets with three replicates, ten snails per replicate, designated as treatment 2 (GNCD) which has groundnut cake, treatment 3 (GLLM) has Gliricidia sepium, treatment 4 (MOLM) has Moringa oleifera, and treatment 5 (LLLM) has Leucaena leucocephala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…The African giant land snail is predominantly favoured in snail farming. Typically, snails consume approximately 3-4% of their body weight in Feed daily (Jimoh & Akinola, 2020). Like other animals, the growth of snails varies depending on their diet.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The African giant land snail is predominantly favoured in snail farming. Typically, snails consume approximately 3-4% of their body weight in Feed daily (Jimoh & Akinola, 2020). Like other animals, the growth of snails varies depending on their diet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, it aids in repairing shell damage resulting from accidents or egg-laying activities. A study by Jimoh and Akinola (2020) investigated the reproductive performance of laying snails (Archachatina marginata) when fed a diet comprising roughages and various concentrate mixes. The research highlighted the necessity for further studies into using compounded rations for snails to address the scarcity of fruits, tubers, and leaves during the dry season.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that larger dimension of the oviduct is needed for snail species with bigger eggs. The higher weight of snails reared High Humidity environment explains their increased oviduct (reproductive) weight and higher number of eggs laid [33].…”
Section: B Reproductive Traitsmentioning
confidence: 99%
“…The productivity of snail farming depends to a great extent on the utilisation of present-day improved techniques and strategies in production which requires gaining information on snails' hatchery, feeding, housing, and marketing of its end products. Ongoing improvement in snail production includes the use of concentrate diets in the feeding of snails and this requires elaborate information from experts (Jimoh and Akinola, 2020). Snails are commonly fed on diets such as fruits of pawpaw, pineapple, banana, pear, oil palm and watermelon and leaves of cassava, pawpaw, cocoyam, and water leaf.…”
Section: Introductionmentioning
confidence: 99%